The impact of athlete burnout on academic burnout among college athletes: a multiple mediation model based on emotion regulation and sleep - Xu, Guihua; Yang, Xirui; Zhang, Qiyong; Li, Chenyang (Frontiers in Psychology, 2025)
BackgroundCollege athletes often face dual demands from training and academics, increasing their risk of both athletic and academic burnout. However, the transfer mechanism between these two forms of burnout remains underexplored, especially regarding the roles of emotional regulation and sleep.MethodsA cross-sectional survey was conducted among 1,918 college athletes using validated self-report measures. Structural equation modeling was applied to examine the direct and indirect effects of college athlete burnout on academic burnout, with cognitive reappraisal and sleep quality as mediators.ResultsCollege athlete burnout significantly predicted academic burnout (β = 0.412, p < 0.001). Both cognitive reappraisal (β = 0.071, p < 0.001) and sleep quality (β = 0.037, p < 0.001) partially mediated this relationship. Additionally, a significant chain mediation pathway was identified through cognitive reappraisal and sleep quality (β = 0.006, p < 0.01), accounting for 1.14% of the total effect.ConclusionAthlete burnout can spill over into academic burnout among college athletes. Beyond confirming this relationship, the study highlights the critical roles of emotional regulation and sleep quality as mechanisms linking the two domains. These findings provide theoretical insight into burnout transfer and underscore the importance of integrating psychological skills training and sleep management into interventions aimed at supporting student-athletes' academic adjustment and mental health.